Development of image processing tools for measurementof beam straightness - Ribeiro, A. Fernando (1993)
The objective was to measure the straightness of steel beams as a non-contact mean and using image processing techniques. This work deals with the development of an image processing methodology to be employed in an inspection machine for measurement of straightness of moving steel beams. The method was embodied in a software that reads the position of the beams, correlates all the positions monitored by the cameras, and reports the quality of straightness of the beam. The inspection machine uses computer vision technology as a non contact measuring device. Video cameras are used to log information about the lateral position and height of steel beams while rolling on a conveyor from the production process. The number of cameras and the distance between them are user defined parameters. The technique developed is prepared to guarantee the measuring system operation if one camera is switched off or fails. This implies the ability of this system on using more than 3 cameras. The system output is the non linearity deviation of the beam, compensating factors for lateral or angular movements in the horizontal measuring plane of the beam and the beam profile. The output is displayed in a computer screen, according to the line method and the least squares method.